Leadership Style and Hospital Performance: Empirical Evidence From Indonesia - Fahlevi, Mochammad; Aljuaid, Mohammed; Saniuk, Sebastian (Frontiers in Psychology, 2022)
The COVID-19 pandemic created new conditions for the functioning of all organizations. Suddenly, there was a problem with the lack of appropriate leadership styles models in health care organizations (hospitals), which are particularly vulnerable to disruptions in a pandemic. Hospitals, in particular, have become exposed to organizational and managerial problems. The article aims to propose an appropriate leadership style model that will guarantee a high level of hospital efficiency, taking into account a pandemic situation in the example of private hospitals in Indonesia. Organizational identification is promoted as a mediating variable due to the high level of this variable in explaining hospital performance in Indonesia based on preliminary studies. During research used a structural equation model using 394 samples at the unit leadership level in private hospitals in Indonesia. The results of this study explain that there is an impact between innovative leadership and strategic leadership styles on hospital performance. Private hospitals in Indonesia need to improve themselves to use the most appropriate leadership style model based on the needs of the hospital itself.